Effect of catalyst on carbon nanotubes synthesis on titanium diboride via chemical vapor deposition. Issue 8 (13th April 2020) - Lin, Jia; Yang, Yihang; Zhang, Houan; Li, Fenqiang; Huang, Guimei; Wang, Jinhuo
Abstract: Carbon nanotubes (CNTs) were in situ synthesized on titanium diboride (TiB2 ) substrates using different catalysts (Fe, Co, and Ni) via ethylene chemical vapor deposition (CVD). The effects of various catalysts on the quality and quantity of grown CNTs were investigated using X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and Raman characterization techniques. Next, as‐received powders were sintered by spark plasma sintering to obtain compact bulk composites. The effects of the metallic catalysts as sintering aids on the microstructural and mechanical properties of TiB2 ‐based composites were also studied. Results show that metal Ni not only plays a significant role in the catalyst to produce larger numbers of CNTs but also promotes the densification of TiB2 ceramics in sintering and has been shown to provide good reinforcement. Maximum values of flexural strength (1093 ± 19 MPa) and toughness (13.9 ± 0.3 MPa ·m 1/2 ) were obtained using the Ni catalyst, which were significantly higher than the same values for Fe and Co catalysts.